Accountability and Transparency of Zakat, Infaq, Shodaqah Fund Management (Case Study on LAZISMU Pasuruan Regency) - Syaifuddin, Muhammad; Khalil, Jafril (ITB AAS INDONESIA Surakarta, 2024)
This study aims to determine the effectiveness of the application of accountability and transparency in the management of zakat, infaq and shodaqah funds at LAZISMU Pasuruan Regency. The method used in this research is a qualitative method with a case study approach. Data collection techniques used in this study include interviews and documentation in the form of financial reports and other supporting documents related to the accountability and transparency of ZIS fund management. Data analysis used data triangulation. The results showed that the form of accountability of LAZISMU Pasuruan Regency, among others: evaluation of board members every month led by the chairman of the board, the existence of ZIS fund management reports in the form of magazines for donors every month and brochures for other than donors, and the existence of audit reports conducted once every 1 month, once every 3 months, once every 6 months conducted by the Muhammadiyah Regional Leadership and once a year conducted by a public accountant. While the forms of transparency of LAZISMU Pasuruan Regency include: in the collection of ZIS funds carried out by means of child philanthropy, socialization through local community activities, and digital fundrising.